2012
DOI: 10.20870/oeno-one.2012.46.4.1529
|View full text |Cite
|
Sign up to set email alerts
|

Effect of canopy management techniques on the nutritional quality of Montepulciano grapevine in Puglia (Southern Italy)

Abstract: <p style="text-align: justify;"><strong>Aims</strong>: Tests were carried out to assess the effects of early defoliation, cluster thinning and cluster cutting on the basic and nutritional composition of musts and wines of <em>Vitis vinifera</em> L. cv. Montepulciano.</p><p style="text-align: justify;"><strong>Methods and results</strong>: Both production and quality variables of the musts were evaluated. Antioxidant activity was determined on berries and on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The wine industry is more and more engaged in research that aims to decrease the content of alcohol in wine, both because it has been part of the question about responsible consumption of alcoholic beverages, and because of the heightened sensitivity of customers about health issues including increased calories intake and risk from alcohol-related illness and disease [1]. A moderate alcohol content is generally defined as 8.5%-12% v/v alcohol and wines with this content can be obtained through several methods applied at different steps of the process, such as canopy management during grape plant life cycle to reduce fermentable sugar concentration in grape [2][3][4][5][6], non-Saccharomyces yeast starters usage during vinification to reduce alcoholic fermentation efficiency [7] and dealcoholisation of wine [8][9][10]. Beside the strategies that involve canopy management of the grapevines, there are other methods that can give results in a less amount of time, they consist in different techniques 2 of 12 that is possible to consider of two distinct groups.…”
Section: Introductionmentioning
confidence: 99%
“…The wine industry is more and more engaged in research that aims to decrease the content of alcohol in wine, both because it has been part of the question about responsible consumption of alcoholic beverages, and because of the heightened sensitivity of customers about health issues including increased calories intake and risk from alcohol-related illness and disease [1]. A moderate alcohol content is generally defined as 8.5%-12% v/v alcohol and wines with this content can be obtained through several methods applied at different steps of the process, such as canopy management during grape plant life cycle to reduce fermentable sugar concentration in grape [2][3][4][5][6], non-Saccharomyces yeast starters usage during vinification to reduce alcoholic fermentation efficiency [7] and dealcoholisation of wine [8][9][10]. Beside the strategies that involve canopy management of the grapevines, there are other methods that can give results in a less amount of time, they consist in different techniques 2 of 12 that is possible to consider of two distinct groups.…”
Section: Introductionmentioning
confidence: 99%
“…Ganichot compared harvest dates from 1945 to 2005 in Chateauneuf du Pape (France) and found that harvest time was getting earlier, advancing from early October in 1945 to early September in 2000 [25]. In recent years, the harvest date of Montepulciano, grown in Abruzzo, advanced by 14-15 days in the central part of the region and by 10 days when grown closer to the coast [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…A three-year study revealed that thinning at 25% and 50% both reduced yield, but only in seasons when yield in the control treatment was highest [41]. Cluster thinning at both 30% and 50% signifcantly improved TSS and pH in Montepulciano in one season [44], whereas thinning across three years showed a more consistent efect of increasing TSS at 50% compared to 25% [41,42]. Reščič et al [42] also revealed a more consistent impact of thinning at 50% at reducing TA than 25%.…”
Section: Introductionmentioning
confidence: 99%
“…Grape producers often remove one cluster per shoot to facilitate ripening, leading to the greater proportion of researchers evaluating cluster thinning near 33-50% severity. Multiple studies have compared thinning at diferent severities [36][37][38][39][40][41][42][43][44][45]. Ough and Nagaoka [40] compared 33% and 66% thinning across multiple years and observed a signifcant decrease in yield in both treatments.…”
Section: Introductionmentioning
confidence: 99%